Boosting 4th Graders' Descriptive Writing Skills with Picture Series at SDIT Al-Lauzah - Rosidah, Siti Latifatul; Setiana Sri Wahyuni Sitepu; Elisa Lestari (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
This study aims to find the improvement in the students' writing descriptive text using picture series at the 4th grade of SDIT Al-Lauzah Tangerang Selatan. This study uses a qualitative descriptive method and implements Class Action Research (CAR) theory. The data is taken from the 4th grade students by giving them a pre-test and post-test and doing some observation in the classroom. The instruments used in this study are picture series and some questionnaire to be given in observation. Then the data is analyzed based on Arikunto’s theory. The result showed that picture series could improve students’ writing descriptive text. It can be seen from the mean of the score in pre-test is 60,1, post-test 1 is 68, and post-test 2 is 74,54. It means there is an increase or significant improvement when pictures series are used as media to improve students’ writing descriptive text. In conclusion, picture series can motivate students to improve the skill of writing descriptive text. The quality of their writing was also increasing. In post-test 2, they used more correct grammatical structure than in pre-test or post-test 1. They can arrange the sentences correctly, use appropriate punctuation, use more new vocabularies in their writing, and describe the picture clearly in the content of their writing.  Finally, this research not only benefits students and teachers at SDIT Al-Lauzah but also offers insights for future research in similar educational contexts. It highlights the potential innovation of teaching method using picture series to make language learning more engaging and effective for students.